Echocardiographic deformation imaging reveals preserved regional systolic function in endurance athletes with left ventricular hypertrophy - Teske, A. J.; Prakken, N. H.; de Boeck, B. W.; Velthuis, B. K.; Doevendans, P. A.; Cramer, M. J. (British Journal of Sports Medicine, 2010)
Background: Left ventricular hypertrophy (LVH) is often observed in athletes, which should be differentiated from hypertrophic cardiomyopathy. The aim of the study was to explore the functional changes measured using tissue Doppler imaging (TDI) deformation analysis in athletes fulfilling LVH criteria participating in different endurance sports.